A Global Reassessment of Solitary-Sociable Dolphins - Nunny, Laetitia; Simmonds, Mark P. (Frontiers in Veterinary Science, 2019)
Dolphins are typically regarded as highly social animals. However, some individuals live apart from their own species and may come to socialize with people through a recognized series of stages which are presented and expanded on in this paper. The term ‘solitary-sociable dolphins’ has been used to describe these animals and such individuals have been identified from several different species and reported in many parts of the world. In many instances, the interactions with people that may follow their original isolation, and which typically become more intense over time, have created situations where the welfare of the animal has been compromised by disturbance, injury, the feeding of inappropriate items and aggressive human behavior. Several solitary-sociable dolphins have also been deliberately injured and killed by humans. People who interact with these dolphins may also put themselves at risk of injury. This paper reports on recent cases drawing on published and unpublished sources. Since 2008, 32 solitary dolphins have been recorded including 27 bottlenose dolphins (25 Tursiops truncatus and two Tursiops aduncus), two striped dolphins and three common dolphins. Four solitary belugas have also been recorded. There are some ten solitary dolphins and one beluga known at the present time. Laws and guidelines currently in place to protect solitary-sociable dolphins need to be strengthened and interactions with people should be avoided or, at the least, carefully managed to protect both the dolphin and the humans involved in the interaction. Terms such as disturbance and harassment which are included in laws need to be clearly defined. Additionally, management plans for solitary-sociable dolphins need to be developed and adapted on a case by case basis taking into account the individual dolphin's sex, age, personality, stage of sociability and home range. It is also important that government officials and local stakeholders work together to implement guidelines which set out how the public can observe or interact with the dolphin safely.